IMPROVING COOPERATION SKILLS THROUGH THE TRADITIONAL GAME OF GOBAK SODOR FOR CHILDREN AGED 5-6 YEARS AT NURUL IMAN MERUYA ISLAMIC KINDERGARTEN IN SOUTH WEST JAKARTA - Shania Kamelia; Sri Nurlaily; Hapsa Kamarudin (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to improve early childhood cooperation skills through the application of the traditional game Gobak Sodor at TK Islam Nurul Iman, Meruya Selatan, West Jakarta. The research employs a Classroom Action Research (CAR) method using the spiral model by Kemmis and McTaggart, conducted over two cycles. The subjects were 20 children in group B, aged 5–6 years. Data were collected through participatory observation using cooperation skill indicators, documentation, and field notes, and were analyzed descriptively using both quantitative and qualitative approaches. The results showed an increase in children's cooperation skills from 35% in the pre-cycle phase to 63% in the first cycle, and further to 91% in the second cycle. Improved cooperation indicators included the ability to share, take turns, help peers, follow rules, and communicate effectively within a group. These findings indicate that Gobak Sodor is an effective and culturally rooted learning medium for fostering social development in early childhood education. The study implies that early childhood educators should integrate traditional games into learning activities to promote cooperative behavior, empathy, and social communication. Teachers are also encouraged to actively guide and reflect on the play process to maximize social development outcomes.